Once-weekly teriparatide improves glucocorticoid-induced osteoporosis in patients with inadequate response to bisphosphonates - Seno, Takahiro (Springerplus, 2016)
BACKGROUND: Patients with glucocorticoid-induced osteoporosis (GIOP) are at very high risk of fracture, and patients with severe GIOP often experience fractures during treatment with bisphosphonates. Teriparatide (TPTD) is the only currently available anabolic agent expected to be effective for GIOP. Once-weekly TPTD decreased bone resorption marker with primary osteoporosis different from daily TPTD, but it has not yet been tested with GIOP. OBJECTIVES: To evaluate the efficacy of once-weekly TPTD for patients with GIOP and inadequate response to bisphosphonates. METHODS: Patients with GIOP and collagen diseases treated with prednisolone for at least 6 months with inadequate responses to bisphosphonates were administered once-weekly TPTD. Bone density of the lumbar spine and femoral neck, measured as percent young adult mean (YAM); serum concentrations of cross-linked N-terminal telopeptides of type I collagen (NTx), bone alkaline phosphatase (BAP), and calcium; and FRAX were measured at baseline and 6, 12 and 18 months after starting TPTD. RESULTS: Of the 12 GIOP patients with collagen diseases enrolled, nine (seven females, two males; mean age 57.4 ± 11.1 years) completed treatment, including six with systemic lupus erythematosus, two with rheumatoid arthritis, and one with adult onset still disease. Only one new fracture event, a lumbar compression fracture, occurred during the study period, although seven patients experienced eight fracture events within 18 months before starting TPTD (p = 0.04). Lumbar spine YAM significantly improved at 18 months (p = 0.04), whereas femoral neck YAM did not (p = 0.477). Serum NTx, BAP, Ca, and FRAX were not significantly affected by TPTD treatment. CONCLUSIONS: Once-weekly TPTD reduces fracture events and increases bone density of the lumbar spine of GIOP patients with inadequate response to bisphosphonates.